Calculation of mass discharge of the Greenland ice sheet in the Earth System Model - O. O. Rybak; E. M. Volodin; A. P. Nevecherya; P. A. Morozova; M. M. Кaminskaya (Лëд и снег)
Mass discharge calculation is a challenging task for the ice sheet modeling aimed at evaluation of their contribution to the global sea level rise during past interglacials, as well as one of the consequences of future climate change. In Greenland, ablation is the major source of fresh water runoff. It is approximately equal to the dynamical discharge (iceberg calving). Its share might have still larger during the past interglacials when the margins of the GrIS retreated inland. Refreezing of the melted water and its retention are two poorly known processes playing as a counterpart of melting and, thus, exerting influence on the run off. Interaction of ice sheets and climate is driven by energy and mass exchange processes and is complicated by numerous feed-backs. To study the complex of these processes, coupling of an ice sheet model and a climate model (i.e. models of the atmosphere and the ocean) in one model is required, which is often called the Earth System Model (ESM). Formalization of processes of interaction between the ice sheets and climate within the ESM requires elaboration of special techniques to deal with dramatic differences in spatial and temporal variability scales within each of three ESM’s blocks. In this paper, we focus on the method of coupling of a Greenland ice sheet model (GrISM) with the climate model INMCM having been developed in the Institute of Numerical Mathematics of Russian Academy of Sciences. Our coupling approach consists in applying of a special buffer model, which serves as an interface between GrISM and INMCM. A simple energy and water exchange model (EWBM-G) allows realistic description of surface air temperature and precipitation fields adjusted to a relief of elevation of the GrIS surface. In a series of diagnostic numerical experiments with the present-day GrIS geometry and the modeled climate we studied sensitivity of the modeled surface mass balance and run off to the key EWBM-G parameters and compared our results with similar model studies. In addition to the atmospheric, oceanic, and ice sheet blocks the ESM normally contains blocks accounting for dynamics of the biosphere, sea ice, hydrological cycle, etc. In practice, application of ESMs for research studies has become possible not long ago owing to the fast progress in computing facilities. Nevertheless, still now ESMs are rather computer time demanding. To provide long runs of a fully coupled ESM at a lower computational cost, we utilized an asynchronous coupling when a 100-yr run of the GrISM corresponds to 1-yr run of the INMCM. The weak point of the numerical experiments is comparison of the results with observations. The lack of observations in Greenland and significant inter-annual variability of air temperature, precipitation, surface melting, and run off do not allow formulation of a reliable reference «climate» and corresponding equilibrium state of GrIS. In practice it means that more or less accurate estimates of the past or future changes of the runoff and total GrIS mass discharge is reasonable to obtain in the form of deviations from a reference undisturbed model state.